STIMULASI PEMBELAJARAN BAHASA ARAB MELALUI ISTIMA DAN TIKRAR UNTUK MENINGKATKAN PEMEROLEHAN KOSAKATA DI LPQ MANSYAUT THULAB MAJALENGKA - Sri Wahyuni, Leny; Vadia Hayya, Anisa (Irfani, 2025)
Many non-formal religious educational institutions, such as madrasah diniyah, Islamic boarding school, and Quranic Education Institution (LPQ), have made Arabic as a mandatory subject. However, the methods commonly used, such as memorizing, tend to be conservative. It made the learning process monotonous and less effective for vocabulary building. To address this, a community service program was conducted at LPQ Mansyaut Thulab Rajagaluh, Majalengka, using istima (listening) and tikrar (repetition) methods to improve vocabulary learning. The program employed a learning service approach to identify challenges and propose practical solutions, including the development of cost-effective learning media to support vocabulary and interactive games to reinforce learned vocabulary. Games, like HTST (Count, Clap, Speak, and Translate), throw the ball, and puzzles, were integrated to make learning enjoyable while accommodating auditory, visual, and kinesthetic learning styles. As a result, students found it easier and faster to grasp new vocabulary, and their enthusiasm for learning increased due to the fun and engaging activities. This initiative not only improved students’ vocabulary acquisition, but also created a dynamic, creative, and effective learning environment tailored to their needs and characteristics.